Computed tomography and magnetic resonance cholangiopancreatography in the assessment of acute pancreatitis - Mustafa Korkut (Universa Medicina, 2020)
BACKGROUND Acute pancreatitis (AP) is a disease associated with sudden onset of abdominal and back pain in a band-like pattern, nausea, and vomiting. In patients with AP, the gold standard, i.e., the initial imaging modality to be used is ultrasonography (US). However, in cases where evaluation is insufficient, computed tomography (CT) and magnetic resonance cholangiopancreatography (MRCP) are other modalities to be applied. In this study, we aimed to demonstrate the diagnostic accuracy of CT and MRCP in patients with acute pancreatitis.